2019
DOI: 10.11594/jtls.09.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Aedes as a Vectors Potential for Dengue Hemorrhagic Fever (DHF) in Semarang City, Indonesia

Abstract: Dengue Hemorrhagic Fever (DHF) is a significant health problem in Semarang, Indonesia. A Certain type of insecticides has been widely applied beginning in the last decade as an effort to control the mosquito vectors of dengue virus. This practice could lead to increased resistance in mosquito populations toward these types of insecticides. This research aimed to describe the resistance status of Aedes sp. populations in Semarang. A cross-sectional design study was conducted in 2015, with Aedes sp. populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…aegypti was occurred in 6 sub-district of Central Java with infection rate among them between 0.48% -8.77% Widiarti (2011), Sayono (2016), and Widiastuti (2016) in Central Java. Martini (2019) also reported the activity of the enzyme monooxygenase in the Aedes aegypti mosquito in Semarang 25 . This enzyme is known to play a role in the metabolism of the pyrethroid insecticides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti was occurred in 6 sub-district of Central Java with infection rate among them between 0.48% -8.77% Widiarti (2011), Sayono (2016), and Widiastuti (2016) in Central Java. Martini (2019) also reported the activity of the enzyme monooxygenase in the Aedes aegypti mosquito in Semarang 25 . This enzyme is known to play a role in the metabolism of the pyrethroid insecticides.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Martini's research (2019) show the activity of the enzyme monooxygenase in the Aedes aegypti mosquito in Semarang 25 .This enzyme is known to play a role in the metabolism of the pyrethroid insecticides. The susceptibility test conducted in Semarang in 2019 also showed that the Aedes aegypti mosquito was still resistant to pyrethroids but susceptible to organophosphates 26 .…”
Section: Resultsmentioning
confidence: 99%
“…People consider temefos to be poisonous, so it is not applied to water reservoirs for consumption. In addition, some residents raise fish in water storage tanks to control mosquito larvae (Martini et al, 2019), (Singh et al, 2011).…”
Section: Ae Aegypti Larvae Resistance Test Against Organophosphate (Temefos)mentioning
confidence: 99%
“…On the other hand, the use of these insecticides, however, has a potential to cause disturbance to the vector. Continuous use of insecticides can lead to vector resistance [2], [3], [4], in addition to having unwanted effects on natural enemies and non-target organisms as well as causing environmental damage [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%